(untitled) (The Reasoner, 2025)
Scientific disconfirmation has often been thought to be reasoning by modus tollens. This interpretation, however, misconstrues the conditionals in this scientific reasoning in terms of the material conditional, rather than in terms of causal conditionals. Scientific confirmation has also been thought to be a logical fallacy, affirming the consequent. Once one embraces the idea that scientists are reasoning in terms of causal conditionals, rather than the material conditional, we can avoid the peculiarity of the view that scientific confirmation is based on a simple logical fallacy. Interpreting scientists as reasoning about physical consequences of hypotheses enables a more charitable interpretation of scientific disconfirmation and confirmation.